Assessment of influence of the program of physical rehabilitation on results of the six-minute test of walking at children with recurrent bronchitis - Marianа Sabadosh (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to estimate efficiency of the carried out program of physical rehabilitation of children with recurrent bronchitis in the conditions of sanatorium. Material & Methods: 109 children of the younger school age are examined. The six-minute test of walking was carried out for the research of functional and adaptation opportunities, and the degree of loading is also estimated on the Borg scale. The obtained data were processed by the adequate methods of mathematical statistics. Results: the improvement of level of the studied indicators at children of the main and control groups is noted after the termination of the course of physical rehabilitation. However, statistically the best dynamics of indicators of length of distance, index of adaptation, index of adaptation of restoration of rhythm and points on the Borg scale are revealed among children of the main groups. Conclusions: the developed and introduced program of physical rehabilitation was more effective in comparison with the standard one.